MarBel Math: Android-Based Electronic Mathematics Book to Enhance Learning Outcomes for Fourth-Grade Students - Dzulfiqar, Miqdad; Bektiningsih, Kurniana (Universitas Pendidikan Ganesha, 2024)
The limitations in providing innovative learning media that align with the developments in Science and Technology negatively impact students, such as difficulty understanding the material, low learning motivation, and poor learning outcomes. This research aims to develop an Android-based electronic book learning media named MarBel Math for flat shapes material in the fourth grade of Elementary School. This research employs the Research and Development (R&D) method with the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques utilize both test and non-test methods. The data analysis technique involves both quantitative and qualitative data analysis methods. The validation results from content experts yielded an average score of 92%, classified as